MAP3K8 Is a Prognostic Biomarker and Correlated With Immune Response in Glioma - Ren, Jing; Xu, Yixin; Liu, Jia; Wu, Sicheng; Zhang, Ruihan; Cao, Haowei; Sun, Jinmin (Frontiers in Molecular Biosciences, 2021)
MAP3K8 is a serine/threonine kinase that widely expressed in immune cell, non-immune cells and many tumor types. The expression, clinical significance, biological role and underlying molecular mechanisms of MAP3K8 in glioma have yet not been investigated. Here, we discovered that MAP3K8 was aberrantly overexpressed in glioma and correlated with poor clinicopathologic features of glioma by analysis from different datasets and immunohistochemistry staining. MAP3K8 is an independent prognostic indicator and significantly correlates with progression of glioma. We also performed the function and pathway enrichment analysis of MAP3K8 in glioma to explore the biological function and underlying molecular mechanisms of MAP3K8 in glioma. MAP3K8 co-expressed genes were mainly enriched in immune-related biological process like neutrophil activation, leukocyte migration, neutrophil mediated immunity, lymphocyte mediated immunity, T cell activation, leukocyte cell-cell adhesion, regulation of leukocyte cell-cell adhesion, B cell mediated immunity, myeloid cell differentiation, regulation of cell-cell adhesion. Single-cell RNA-sequencing data and immunohistochemistry analysis demonstrated that MAP3K8 expressed in malignant and immune cells, and mainly enriched in microglia/macrophage cells of glioma. Expression of MAP3K8 was positively correlated with immune infiltration including T cells CD4+ effector memory, plasmacytoid dendritic cell, neutrophil, myeloid dendritic cell, mast cellsand macrophage in glioma. Further correlation analysis demonstrated that a series of inhibitory immune checkpoint molecules, chemokine and chemokine receptor was positively correlated with MAP3K8 expression.. MAP3K8 might play an essential role in tumor immunity and inhibition of MPA3K8 is a plausible strategy for the glioma immunotherapy.